Strengthening the international employment regime - Steve Charnovitz (Intereconomics, 1995)
Although the idea of coordinating national employment policies goes back to the beginning of the 20th century, little progress has occurred in recent decades. The purpose of this article is to explain why such coordination is needed and how it should be accomplished.
Keywords: 330; Employment